The Synbiotic Effect Of Volaticle Oil Extracted From Leaves Rosmarinus Officinolis And Nigellai Sativa On Microbial And Sensory Characteristics Of Minced Poultry Meat During Cold Storage (Baghdad Science Journal, 2016)
The objective of present study was to investigate the effect of using duplex volaticle oil of Rosmarinusoficinolis and Nigella sativain microbial quality, sensing and extending storage time of minced cold poultry meat. Duplex volaticle oil was added at 25, 50 and 75 mg/kg to minced poultry meat , these treatments were stored individually for (0 ,4 and 7) days at( 4-7) C0 . After making several microbial and sensing test. The following results were obtained:-The process of adding duplex volaticle oil of Rosmarinus officinolis and Nigella sativa to minced poultry meat led to significant reduced (P